The Armenian Repatriation 1908-1914,The Question of Nationality and Property - Hale şıvgın; Meryem Günaydın (Gazi Akademik Bakış)
By the rise of the industrial America, the prosperous living conditions in the United States has begun to pull immigrants and hard economic conditions became a powerful driving force behind the immigration. Ottoman emigration to America has approximately the 80-90-year-old history. Ottoman emigration to America has continued between 1908-1914 years even after the Committee of Union and Progress (CUP) issued the proclamation of the Constitution. Another feature of migrations in this period, the return of Armenians previously migrated from where they went. This study focused on repatriation of Armenians from United States. The population emigrated from Ottoman Empire to America has been encouraged to return under Tashnak political campaigns. It has been tried to get the picture of repatriation campaigns and politics regarding Armenians and after returnees how the question of nationality and property has been solved by CUP.